Quantitative and enantioselective analysis of monoterpenes from plant chambers and in ambient air using SPME - Yassaa, N.; Custer, T.; Song, W.; Pech, F.; Kesselmeier, J.; Williams, J. (ATMOSPHERIC MEASUREMENT TECHNIQUES, 2010)
A headspace solid-phase microextraction (HS-SPME) and gas chromatography/mass spectrometry (GC/MS) system has been developed for quantifying enantiomeric and nonenantiomeric monoterpenes in plant chamber studies and ambient air. Performance of this system was checked using a capillary diffusion system to produce monoterpene standards. The adsorption efficiency, competitive adsorption and chromatographic peak resolution of monoterpene enantiomer pairs were compared for three SPME fibre coatings: 75 mu m Carboxen-PDMS (CAR-PDMS), 50/30 mu m divinylbenzene-carboxen-polydimethylsiloxane (DVB-CAR-PDMS) and 65 mu m divinylbenzene-polydimethylsiloxane (DVB-PDMS). Key parameters such as the linearity and reproducibility of the SPME system have been investigated in this work. The best compromise between the enantiomeric separation of monoterpenes and competitive adsorption of the isoprenoids on the solid SPME fibre coating was found for DVB-PDMS fibres. The optimum conditions using DVB-PDMS fibres were applied to measure the exchange rates of monoterpenes in the emission of Quercus ilex using a laboratory whole plant enclosure under light and dark conditions, as well as in ambient air. With 592 and 223 ng m(-2) s(-1) respectively, beta-myrcene and limonene were the predominant monoterpenes in the emission of Q. ilex. These values were closely comparable to those obtained using a zNose and cartridge GC-FID systems.
The following values have no corresponding Zotero field: pub-location: BAHNHOFSALLEE 1E, GOTTINGEN, 37081, GERMANY publisher: COPERNICUS GESELLSCHAFT MBH
Keywords: GC/MS; Quercus ilex

Biomonitoring of Atmospheric PAHs by Evergreen Plants: Correlations and Applicability - Librando, V; Perrini, G; Tomasello, M (Polycyclic Aromatic Compounds, 2002)
This article deals with looking for the best passive samplers among eleven plants diffused in the Mediterranean basin for the determination of polycyclic aromatic hydrocarbons in the atmosphere in substitution to the particulate matter sampling. The most recent research about biological passive samplers showed a quali-quantitative difference in pollutant sampling by different plants. Evergreen trees with long-lived leaves were selected in the urban area of Catania (Italy) and both samples (leaves and particulate matter) were extracted and purified by a two stage method before the analysis was performed by a GC/MS. Leaves and particulate matter were sampled in three different seasons (winter, spring and summer). PAHs concentrations found in the particulate matter and leaves were correlated. Some plants ( Olea europaea and Quercus ilex ) showed high values (r 2 > 0.85) of linear correlation coefficient in all seasons and are characterized by profiles similar to that of the particulate matter. Further, it has been observed that during the warmer seasons the total quantity of PAH adsorbed by the plants is greater but the fitting is better during winter. No difference was found by washing leaves with distilled water: this means that PAHs aren't deposited on the surface but are adsorbed in the lipidic layer of the leaves.
doi: 10.1080/10406630213563
Keywords: correlation; GC/MS; leaves; PAH; particulate matter; passive samplers

Biomonitoring of Atmospheric PAHs by Evergreen Plants: Correlations and Applicability - Librando, V.; Perrini, G.; Tomasello, M. (Polycyclic Aromatic Compounds, 2002)
This article deals with looking for the best passive samplers among eleven plants diffused in the Mediterranean basin for the determination of polycyclic aromatic hydrocarbons in the atmosphere in substitution to the particulate matter sampling. The most recent research about biological passive samplers showed a quali-quantitative difference in pollutant sampling by different plants. Evergreen trees with long-lived leaves were selected in the urban area of Catania (Italy) and both samples (leaves and particulate matter) were extracted and purified by a two stage method before the analysis was performed by a GC/MS. Leaves and particulate matter were sampled in three different seasons (winter, spring and summer). PAHs concentrations found in the particulate matter and leaves were correlated. Some plants ( Olea europaea and Quercus ilex ) showed high values (r 2 > 0.85) of linear correlation coefficient in all seasons and are characterized by profiles similar to that of the particulate matter. Further, it has been observed that during the warmer seasons the total quantity of PAH adsorbed by the plants is greater but the fitting is better during winter. No difference was found by washing leaves with distilled water: this means that PAHs aren't deposited on the surface but are adsorbed in the lipidic layer of the leaves.
doi: 10.1080/10406630213563doi: 10.1080/10406630213563The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: correlation; GC/MS; leaves; PAH; particulate matter; passive samplers

Identification of the main fatty acids component of the cork suberine by GC/MS - Bleton, J; Mejanelle, P; Goursaud, S; Tchapla, A (ANALUSIS, 1998)
The aim of this work was to verify the presence of cork (Quercus Suber) in two samples of linoleum the beginning of the twentieth century Using GC/MS after acidic methanolysis and silylation, it was possible to identify most of the components of a modern sample of cork. The dominant is a lipid polymer: the suberin. Its monomeric composition is examined in details.
APS
Keywords: Cork; GC/MS; Quercus suber L.; suberin

Identification of the main fatty acids component of the cork suberine by GC/MS - Bleton, J.; Mejanelle, P.; Goursaud, S.; Tchapla, A. (ANALUSIS, 1998)
The aim of this work was to verify the presence of cork (Quercus Suber) in two samples of linoleum the beginning of the twentieth century Using GC/MS after acidic methanolysis and silylation, it was possible to identify most of the components of a modern sample of cork. The dominant is a lipid polymer: the suberin. Its monomeric composition is examined in details.
APSAPSThe following values have no corresponding Zotero field: pub-location: 7, AVE DU HOGGAR, PARC D ACTIVITES COURTABOEUF, BP 112, F-91944 LES ULIS CEDEXA, FRANCE publisher: E D P SCIENCES
Keywords: Cork; GC/MS; Quercus suber L.; suberin